Biomarker-driven therapy in endometrial cancer. Issue 3 (6th March 2023) - Karpel, Hannah; Slomovitz, Brian; Coleman, Robert L; Pothuri, Bhavana
Abstract : This article reviews treatments and targets of interest in endometrial cancer by molecular subtype. The Cancer Genome Atlas (TCGA) classifies four molecular subtypes—mismatch repair deficient (dMMR)/microsatellite instability-high (MSI-H); copy number high (CNH)/p53abn; copy number low (CNL)/no specific molecular profile (NSMP); and POLEmut—which are validated and highly prognostic. Treatment consideration by subtype is now recommended. In March and April 2022, respectively, the US Food and Drug Administration (FDA) fully approved and the European Medicines Agency adopted a positive opinion recommending the anti-programmed cell death protein-1 (PD-1) antibody pembrolizumab for advanced/recurrent dMMR/MSI-H endometrial cancer which has progressed on or following a platinum-containing therapy. A second anti-PD-1, dostarlimab, received accelerated approval by the FDA and conditional marketing authorization by the European Medicines Agency in this group. The combination of pembrolizumab/lenvatinib for mismatch repair proficient/microsatellite stable endometrial cancer, including p53abn/CNH and NSMP/CNL, received accelerated FDA approval in conjunction with Australia's Therapeutic Goods Administration and Health Canada in September 2019. The FDA and European Medicines Agency made full recommendations in July 2021 and October 2021. Trastuzumab is National Comprehensive Cancer Network (NCCN) compendium listed for human epidermal growth factor receptor-2-positive serous endometrial cancer, which is primarily within the p53abn/CNH subtype. In addition to hormonal therapy, maintenance therapy with selinexor (exportin-1 inhibitor) showed potential benefit in p53 -wildtype cases in a subset analysis and is being investigated prospectively. Other treatment regimens being evaluated in NSMP/CNL are hormonal combinations with cyclin-dependent kinase 4/6 inhibitors and letrozole. Ongoing trials are evaluating immunotherapy in combination with frontline chemotherapy and other targeted agents. Treatment de-escalation is being evaluated in POLEmut cases given its favorable prognosis with or without adjuvant therapy. Molecular subtyping has important prognostic and therapeutic implications, and should guide patient management and clinical trial design in endometrial cancer, which is a molecularly driven disease.